Reseña/Review (D'Alisa, G., Demaria, F., Kallis, G. (eds.), "Degrowth: a vocabulary for a new era". Milton Park: Routledge, ISBN: 978-1-138-00077-3 (pbk), 215 págs., 2014) - Prádanos, Luis I. (Teknokultura. Revista de Cultura Digital y Movimientos Sociales, 2017)
Reseña/Review (D'Alisa, G., Demaria, F., Kallis, G. (eds.), "Degrowth: a vocabulary for a new era". Milton Park: Routledge, ISBN: 978-1-138-00077-3 (pbk), 215 págs., 2014)